Can synaptophysin be used as a marker of breast cancer diagnosed by core‐needle biopsy in epithelial proliferative diseases of the breast?. Issue 7 (29th May 2016) - Maeda, Ichiro; Tajima, Shinya; Ariizumi, Yasushi; Doi, Masatomo; Endo, Akira; Naruki, Saeko; Hoshikawa, Masahiro; Koizumi, Hirotaka; Kanemaki, Yoshihide; Ueno, Takahiko; Tsugawa, Koichiro; Takagi, Masayuki
Abstract: The differential diagnosis of epithelial proliferative disease using core needle biopsy (CNB) is problematic because it is difficult to differentiate between intraductal papilloma, ductal hyperplasia, ductal carcinoma in situ, and invasive ductal carcinoma. Many studies have reported that breast cancer lesions are positive for neuroendocrine (NE) markers, whereas only a small number of studies have reported immunopositivity for NE markers in normal mammary tissues or benign lesions. We asked whether NE factors could be used as markers of breast cancer. We determined the immunopositivity rate of synaptophysin, an NE marker, in 204 lesions excised from the breast using CNB in patients who visited a university‐affiliated comprehensive medical facility and examined whether synaptophysin is a marker of breast cancer. The specimens were classified as synaptophysin‐negative cases (56 benign, 99 malignant); equivocal cases (<1 %: 2 benign, 15 malignant); and synaptophysin‐positive cases (1 benign, 31 malignant). The sensitivity, specificity, positive predictive value, and negative predictive value for malignancy of the lesions classified as synaptophysin positive were 23.3 %, 98.2 %, 96.9 %, and 36.1 %, respectively. The respective values for lesions classified as equivocal were 11.6 %, 96.6 %, 88.2 %, and 36.1 %. Synaptophysin may provide a marker of breast cancer diagnosed by CNB.